(untitled) (Bangladesh Journal of Botany, 2020)
Effects of four different levels of NaCl (05, 10, 15, 20 dS/m) on the seed germination of cluster bean (Cyamopsis tetragonoloba L.) cultivars were investigated. Only distilled water was used in the control. The experiment was conducted in the Petri dishes under laboratory condition and laid out in CRD comprising five replicates. The results indicated that the germination index (GI), seed vigor index (SVI), germination stress index and seedling length (radicle and plumule) decreased with increase of salinity levels and germination percentage (GP) was reduced significantly at the highest level of salinity (200 mM). However, mean germination time (MGT) and time taken for 50% germination (T50) increased by increasing salinity levels. Correlation coefficient between all possible combinations was estimated and the results indicated that GP, GI, MGT, T50, and SVI had significant positive or negative correlation with each other.